The farmer behavior using pesticide in maize plantation. Issue 2 (July 2021) - Wirasti, D; Aminah, S N; Abdullah, T; Fatahuddin,; Yuliani,
Abstract: Pesticide is poisonous compound containing synthetic chemicals and popularly used by farmers in crop management. The harmful synthetic chemicals contained in pesticides are capable of rapidly killing target organisms. However, the continuous use of pesticides killing natural enemies as the potential agent to control insect pests. Another risks the pesticide residues become the main source of environmental pollution. The research objective is to determine the behavior of farmers using pesticides in maize plantation. The research was conducted in Tenri Pakkua village, Lappariaja district, Bone Regency, South Sulawesi from January to March 2020. The research activity used a survey method in the form of interviews using a questionnaire to 35 respondent farmers. The results were showed about 97.15% of respondent control weeds using herbicides, about 2.85% of respondents control manual for the same weed. In addition, 62.86% of the respondent used herbicides for more than four years. The most insecticides used by respondents control insect pests in maize from the active ingredients: Permethrin (42.87%), Fipronil (14.29%), Lambda-cyhalothrin (11.44%) and Metomil (8, 58%). The results showed that farmers prefer use pesticides in the form of herbicides and synthetic insecticides because the results are visible, they quickly kill the target organism, the application does not require special skills and is easy to obtain (commercially available).